Effects of Van Hiele's phases of learning and theory of geometry thinking on geometry learning of Malaysian year five students - Tan, Tong Hock (2016)
This study investigates the effects of van Hiele’s phases of learning strategy and levels of geometry thinking strategy using Google SketchUp in teaching of geometry, one of the areas in the scope on ‘Shapes and Spaces’ for Integrated Curriculum for Primary School. The study has three purposes. Firstly, identifying strategy that can help improve students’ van Hiele’s levels of geometry thinking in the learning of geometry at primary level. Secondly, determining students’ spatial visualization ability, conceptual knowledge, procedural knowledge and performance in geometry. Thirdly, identifying the extent of effectiveness of van Hiele’s theory in helping students in the learning of geometry. The results of the study support van Hiele’s theory that student development in geometry is sequential from one level of thinking to the next without skipping any level. The development depends on the content and method of instruction but not on their age. The first phase of the study involves development of the learning modules. ADDIE Model was adopted and implemented based on the required steps which are analysis, design, development, implementation and evaluation. The van Hiele’s Phases of Learning Module (VH-PL) and van Hiele’s Levels of Geometry Thinking using Google SketchUp Module (VH-GSU) consist of four units which include Three Dimensional Shapes, Triangles, Squares and Rectangles, Cubes and Cuboids. Each of the modules incorporates relevant content and instruction which are designed to be executed with van Hiele’s development of geometry thinking and constructivist approach. For each module, students executed specific tasks in specific order which were aimed to assist them to progress through the first three levels of van Hiele’s geometry thinking. The study had adopted a randomized pre and post true-experimental design using three different groups of subjects. It was conducted to test the effects of the use of the modules on van Hiele’s levels of geometry thinking, spatial visualization ability, conceptual knowledge and procedural knowledge. Data was collected before and after the use of modules. The 96 Year five participants of the study were randomly assigned into three equivalent groups to learn the selected geometry topics. The first group was exposed to the conventional learning strategy, the second group used the van Hiele’s Phases Learning strategy and the third group used the van Hiele’s Levels of Geometry Thinking using Google SketchUp strategy. Data was collected using Wu’s Geometry Test, Spatial Visualization Ability Test and Geometry Achievement Test which includes measurement for conceptual knowledge and procedural knowledge. The analyses revealed that the use of the van Hiele’s Phases of Learning and Levels of Geometry Thinking using Google SketchUp modules assisted majority of the students to progress through their first three van Hiele’s levels of geometry thinking with most of the progression occurring in sequential order. This study also underlay a framework to capitalize van Hiele’s theory in developing teaching materials using technology or without technology as a practical alternative in assisting learners to progress through the levels of van Hiele’s geometry thinking and ultimately reducing their learning difficulties in geometry. The study showed that there were significant differences in students’ spatial visualization ability (p=.000 < .05), conceptual knowledge (p=.000 < .05), procedural knowledge (p=.000 < .05) and performance as a result of learning geometry using the modules developed. Finally, the study has proven that teaching based on interaction of van Hiele’s theory, constructivism theory and principles of spatial visualization ability, conceptual knowledge and procedural knowledge make learning geometry easier for the students, thus improving their spatial visualization ability, conceptual knowledge, procedural knowledge and van Hiele’s levels of geometry thinking.